Nurses' competency in Saudi Arabian healthcare context: A cross‐sectional correlational study - Evelyn E. Feliciano; Alfredo Z. Feliciano; Jestoni D. Maniago; Ferdinand Gonzales; Adelina M. Santos; Abdulrhman Albougami; Mehrunnisha Ahmad; Hadeel Al‐Olah (Wiley, 2021)
Abstract Aim To measure the competence and characteristics of nurses in Saudi Arabia delivering health care with significant correlations. Design A cross‐sectional correlational study. Methods Data were collected in 2019 using a standardized questionnaire, Competency Inventory for Registered Nurses (CIRN), that included a purposive sample of 621 nurses working in Saudi Arabia. Results A positive evaluation of nurses' overall core competency components is recognizably measured with greater competency levels in their workplace, scoring highest in "legal/ethical practice" while "critical thinking and research aptitude" represented the lowest dimension. Nurses' marital status, years of graduation, length of service, duty hours and nurse-patient ratio affect their competency level. Nurses' competence and their sociodemographic characteristics are significantly correlated attributes. Medical ward nurses are likely to have the greatest competence in delivering safe nursing care within training's legal borders.